(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the mechanism of making decisions with their direct participation, taking into account the initiatives of citizens, the allocation of a part of the budget funds and the selection of directions for spending these funds, and the mechanism of the implementation of the adopted decisions. Statistical analysis and suggestions are also included.